Ways of Being an Author in Consumer Society: The Autofiction Narratives of Pedro Juan Gutiérrez. Issue 10 (26th November 2021) - Casas, Ana
Abstract: Among other questions on the figure of the author, many autofictional protagonists are made to ponder the place occupied by the author in an industry in which cultural goods are increasingly classified as merchandise made available for consumption. The mechanisms by which autofiction deconstructs the 'romantic' conception of the author as an original, unique and autonomous being, instead presenting them as another agent in the cultural and literary system, will be analysed based on the above idea. We will focus our attention on the example of Pedro Juan Gutiérrez's autofictional texts.